Monitoring Apnea of Prematurity: Validity of Nursing Documentation and Bedside Cardiorespiratory Monitor - Amin, Sanjiv B.; Burnell, Erica (American Journal of Perinatology, 2013)
Objective To compare apnea events recorded by bedside cardiorespiratory monitor and nursing documentation with those detected by visual inspection of continuous electronic cardiorespiratory waveform.Methods In a prospective observational study, 20 nonventilated infants of 28 to 33 weeks' gestational age were monitored for apnea during the first 2 postnatal weeks. Apnea was defined as a respiratory pause > 20 seconds or > 15 seconds if associated with a heart rate < 80/min or oxygen saturation < 85%. True apnea was defined as one for which visual inspection of continuous electronic cardiorespiratory waveform on the central monitor verified apnea.Results The number of apnea episodes recorded by nursing documentation and bedside monitors were 207 and 418, respectively. Only 7.7% of apnea events recorded by nursing documentation were confirmed as true apnea compared with 50.4% of apnea recorded by bedside monitors and the difference was statistically significant. Of true apnea (n = 211) episodes recorded on central monitors, 99% were recorded by bedside monitors but only 7.6% of apnea occurrences were recorded by nursing personnel.Conclusions Nursing documentation does not provide accurate monitoring of apnea. Although bedside monitors have better sensitivity and specificity than nursing documentation, future research should be directed to improve the specificity of bedside monitoring.
Keywords: neonatal intensive care unit; bradycardia; desaturation; premature infants